Phenotypic differences and transcriptomic analysis of extreme plant heights in a hybrid population of Hedychium - Xuanguo LIANG; Fang WANG; Yunyi YU; Yanping FAN (Huanan Nongye Daxue xuebao, 2025)
ObjectiveThere were significant differences in plant height within the F1 hybrid population derived from the cross between Hedychium ‘Baitai’ and H. gardnerianum. This study was aimed to identify key genes regulating plant height of Hedychium through phenotypic and transcriptome sequencing (RNA-seq) analyses, thereby providing an important reference basis for the molecular breeding and plant architecture improvement of Hedychium. MethodThe twenty tallest and twenty shortest plants in the Hedychium hybrid population were selected for statistics of plant height, internode length, and internode cell length. The aboveground stem was partitioned into A–D segments, and correlation analysis was performed to determine the factors influencing plant height variation. By comparing and analyzing the differences in internode length and internode cell length, the growth parts with differences were determined. RNA-seq was used to detect the mRNA expression levels of the differential growth parts of the tall and dwarf individual plants. Bioinformatics tools were employed to screen differentially expressed genes (DEGs). Combined with literature support, genes related to plant height regulation were screened, and verified by qRT-PCR. ResultThere was a significant positive correlation between the internode length and internode cell length of plants in the Hedychium hybrid population. The differences in internode length and internode cell growth in the C segment between tall and dwarf plants were the most significant. A total of 269 DEGs were identified through RNA-seq analysis of the plant with tall and dwarf phenotypes. Thirteen genes related to plant height regulation with significant differential expression were screened out based on transcriptome data. Among them, HcMYB136, HcNAC140, HcEXPA4, HcEXPB3, HcXTH28, HcXTH8, HcCYCB1-1 and HcCYCD3-2 were down-regulated in the three extremely dwarf plants, while HcMYB238, HcMYB254, HcNAC126, HcbZIP50 and HcCDC27B were up-regulated in the three extremely dwarf plants. The qRT-PCR results showed that the expression change trends of these 13 genes were highly consistent with the transcriptome data. ConclusionThe main influencing factor for the phenotypic variation of the extreme plant height in the Hedychium hybrid population is the internode cell length, and the growth differences in the C segment of the tall and dwarf plants are the most significant. The phenotypic differences of the extreme plant height of Hedychium are a complex biological process, which may be caused by the coordinated regulation of multiple genes.